7 Generations : a Plains Cree Saga - Robertson, David Alexander (Portage & Main Press, 2012)
7 Generations: A Plains Cree Saga originally published as a four-part graphic novel series; Stone, Scars, Ends/Begins, and The Pact. This graphic novel follows one Plains Cree family from the early 19th century to present day. For Edwin, the story of his ancestors from both the distant and recent past must guide him through an uncertain present, to the dawn of a new future. 7 Generations explores the life of Stone, a young Cree warrior, the smallpox epidemic of 1870, the residential school system of the 20th century and its familial legacy.